Engineering Philadelphia : The Sellers Family and the Industrial Metropolis - Vitiello, Domenic (Book collections on Project MUSE., 2013)
The Sellers brothers, Samuel and George, came to North America in 1682 as part of the Quaker migration to William Penn's new province on the shores of the Delaware River. Across more than two centuries, the Sellers family--especially Samuel's descendants Nathan, Escol, Coleman, and William--rose to prominence as manufacturers, engineers, social reformers, and urban and suburban developers, transforming Philadelphia into a center of industry and culture. They led a host of civic institutions including the Franklin Institute, Abolition Society, and University of Pennsylvania. At the same time, their vast network of relatives and associates became a leading force in the rise of American industry in Ohio, Georgia, Tennessee, New York, and elsewhere. Engineering Philadelphia is a sweeping account of enterprise and ingenuity, economic development and urban planning, and the rise and fall of Philadelphia as an industrial metropolis. Domenic Vitiello tells the story of the influential Sellers family, placing their experiences in the broader context of industrialization and urbanization in the United States from the colonial era through World War II. The story of the Sellers family illustrates how family and business networks shaped the social, financial, and technological processes of industrial capitalism. As Vitiello documents, the Sellers family and their network profoundly influenced corporate and federal technology policy, manufacturing practice, infrastructure and building construction, and metropolitan development. Vitiello also links the family's declining fortunes to the deindustrialization of Philadelphia--and the nation--over the course of the twentieth century.